2021
DOI: 10.1103/physrevmaterials.5.064416
|View full text |Cite
|
Sign up to set email alerts
|

Cation and anion topotactic transformations in cobaltite thin films leading to Ruddlesden-Popper phases

Abstract: Topotactic transformations involve structural changes between related crystal structures due to a loss or gain of material while retaining a crystallographic relationship. 2The perovskite oxide La0.7Sr0.3CoO3 (LSCO) is an ideal system for investigating phase transformations due to its high oxygen vacancy conductivity, relatively low oxygen vacancy formation energy, and strong coupling of the magnetic and electronic properties to the oxygen stoichiometry. While the transition between cobaltite perovskite and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Phase transformation has also been realized in La 0.7 Sr 0.3 CoO 3−δ -specifically, a series of topotactic transitions from the equilibrium ferromagnetic metallic perovskite structure (δ ≈ 0) to an antiferromagnetic semiconducting brownmillerite structure (δ = 0.5) and further to a weakly ferromagnetic insulating Ruddlesden-Popper structure (La 1.4 Sr 0.5 Co 1+ν O 4−δ ). 47 A similar transition was also observed between the equilibrium brownmillerite SrCoO 2.5 phase to the metastable SrCoO 3 phase. [48][49][50] Oxygen vacancy concentrations in the cobaltites have been varied in multiple ways, e.g., by depositing oxygen-scavenging metals, 51 annealing in reducing environments, 49 using electric fields, 50 and with epitaxial strain.…”
Section: A Metal-insulator Transitions In Quantum Materialssupporting
confidence: 60%
“…Phase transformation has also been realized in La 0.7 Sr 0.3 CoO 3−δ -specifically, a series of topotactic transitions from the equilibrium ferromagnetic metallic perovskite structure (δ ≈ 0) to an antiferromagnetic semiconducting brownmillerite structure (δ = 0.5) and further to a weakly ferromagnetic insulating Ruddlesden-Popper structure (La 1.4 Sr 0.5 Co 1+ν O 4−δ ). 47 A similar transition was also observed between the equilibrium brownmillerite SrCoO 2.5 phase to the metastable SrCoO 3 phase. [48][49][50] Oxygen vacancy concentrations in the cobaltites have been varied in multiple ways, e.g., by depositing oxygen-scavenging metals, 51 annealing in reducing environments, 49 using electric fields, 50 and with epitaxial strain.…”
Section: A Metal-insulator Transitions In Quantum Materialssupporting
confidence: 60%
“…We now turn to discuss the effect of the local defect structure on several geometrical parameters, including the lattice parameter, which was suggested as a fingerprint of oxygen vacancy concentration in previous experimental studies. , XRD reciprocal space maps show that the thin films are coherently strained to the underlying LSAT substrate . Therefore, we only consider the change in the lattice parameter in the direction perpendicular to the interface (Δ d out‑of‑plane ), with the in-plane lattice parameters corresponding to that of the LSAT substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The films were cooled slowly to room temperature after the deposition with an oxygen pressure of 300 Torr to ensure as few oxygen vacancies as possible (δ is expected to be <0.04 in the deposited thin film). The LSCO films were annealed either in a gas evolution system , or a Mg-based oxygen trap system . In the gas evolution system, the base pressure was maintained at ∼10 –10 atm, and high-purity oxygen (>99.99%) of different partial pressures ranging from 10 –12 to 10 –7 atm was introduced using a computer-controlled metal-seated valve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of nanostructure morphology, the main focus has been surface-anchored nanostructures for catalysis; however, several researchers have also reported bulk (i.e., sub-surface) exsolution of embedded nanostructures. [54][55][56] Dai, Pan, et al concluded based on in situ TEM studies of Rh exsolution from CaTiO 3−δ that initial-stage exsolution created nanostructures embedded in the perovskite matrix, making them inaccessible during heterogeneous catalysis. 53 Kim, Choi, et al reported STEM dark field images clearly showing bulk exsolution of Ni particles throughout the thickness of epitaxially grown La 0.2 Sr 0.7 Ti 0.9 Ni 0.1 O 3−δ thin films, but did not interrogate these nanostructures beyond nanometer-scale energy dispersive spectroscopy (EDS) line profiles confirming the presence of Ni.…”
Section: Introductionmentioning
confidence: 99%